Konsep Toleransi Nilai Moderasi dalam Menanggapi antara Perbedaan dan Penyimpangan Prespektif Islam - Sholahuddin Qoffal; Waqiatul Masrurah; Lailatul Firdausi; Hamdani Hamdani (Institut Nurul Islam Mojokerto, 2025)
This study investigate how the genuine meaning of tolerance is understood. This study's major goal is to draw attention to instances when the Islamic concept of moderation tolerance is not being applied correctly. The method used in this study is a qualitative method with a descriptive approach consisting of two sources: phenomena occurring in the field and news on social media, such as Muslims participating in other religious worship, which serve as primary data, and books or journals related to the discussion of tolerance, which serve as secondary data. The research results show that there is a lot of tolerance being applied beyond religious boundaries, which distinguishes between differences that deserve to be respected and deviations that need to be corrected. Actions such as participating in the worship of other religions are considered to violate the principles of Islamic faith and can damage the purity of the teachings. A proper understanding of moderation must be based on a balance between an open attitude and steadfast adherence to Islamic teachings. Well-applied religious moderation will have an influence in reconciling conflict, strengthen social bonds, and open the doors of guidance from non-Muslims. This is important to understand so that Muslims can wisely apply the principles of moderation and tolerance in accordance with the moderation that aligns with Islamic teachings